PENGARUH CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY INSTITUT FRANÇAIS INDONESIA DI SURABAYA - Tanti Utami Dewi; Priyambodo Nur Ardi Nugroho (Program Studi Teknologi Informasi, 2020)
French as the second official language in the United Nations plays an essential rule in communication as a foreign language among professional and intercommunication. Institut Français Indonesia in Surabaya has an essential role in providing quality and reliable French language courses. Its presence during these five decades was so meaningful to Surabaya until early 2012, and the French government decided to make changes in the management and implementation of operational policies. Background of the research on the effect of customer experience on customer satisfaction and customer loyalty Institut Français Indonesia in Surabaya was based on the declining number of students during 2012-2014. In this study, 66 students from the advanced class in May and June as respondents. The results of this study were analyzed using path analysis. Customer experience significant effect on customer satisfaction directly by 0.967 with a positive direction, as well as the customer experience significant effect on customer loyalty directly at 0.479 with the positive direction. Customer satisfaction has a significant effect on customer loyalty at 0.485 with positive direction. P